Solve the system of equations by substitution:

2x+5y=3 (1)

x-3y=7 (2)

Solve (2) for x.

x=7+3y (3)

Substitute (3) in (1)

(2)(7+3y)+5y=3

14+6y+5y=3

11y=-11

y=-1

Substitute 1 for y in (3)

x=7+3(-1)

x=4

Verify by substituting 4 for x and -1 for y in (1)

(2)(4)+5(-1)=3

8-5=3

**Thus x=4 and y=-1**

Solve the second system of equation by elimination. Write the equations in standard form.

2x+3y=11 (1)

3x-y=-11 (2)

Multiply (2) by 3 and subtract from (1)

2x+3y=11

9x-3y=-33

------------

11x=-22

x=-2

Substitute -2 for x in (2)

(3)(-2)-y=-11

-6-y=-11

y=11-6=5

Verify by substituting -2 for x and 5 for y in (1)

2(-2)+3(5)=11

-4+15=11

**Thus x=-2 and y=5**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now